How the mind perception of artificial intelligence in smart devices affects customer-brand relationships - Guerreiro, J.; Loureiro, S. M. C. (AIRSI2020 Conference Proceedings, 2020)
Artificial Intelligence (AI) has grown from an established science with active research focused on improving its techniques and algorithms to being embedded in our daily lives. In 2022, the investment on AI systems is expected to reach a total of $77.6 billion (IDC, 2019) and today, there are many examples of AI systems being embedded in self-driving cars, surveillance cameras and in voice-assistant smart devices. Despite the concerns regarding data privacy, consumers value the benefits of an integrated smart society that reduces the effort of repetitive tasks and increases convenience and performance (TechCrunch, 2019).